HUBUNGAN ANTARA PERKEMBANGAN KOGNITIF SISWA DENGAN KARAKTER DISIPLIN SISWA DI SMA - Putri, Fhadira Insani; Triani, Elza (EduFisika: Jurnal Pendidikan Fisika, 2023)
Effective student cognitive development can be seen when students are in junior high school. This study aims to answer the research question, namely how is the relationship between cognitive development variables and the disciplinary character of high school students in physics subjects. The method used in this research is a mixed quantitative and qualitative method with a total of 50 students. The results of the study are the correlation test which states that the relationship with the data results is less than 0.05, which means that there is a relationship between the two variables tested. The conclusion of this study is that there is a relationship between cognitive development and the disciplinary character of high school students in physics subjects. The novelty of this study is that no comparisons were made for different schools to find out the relationship between cognitive development variables and disciplinary character. The limitations of this study are only comparing two classes.